Training of Dental Professionals in Motivational Interviewing can Heighten Interdental Cleaning Self-Efficacy in Periodontal Patients - Woelber, Johan P.; Spann-Aloge, Narin; Hanna, Gilgamesh; Fabry, Goetz; Frick, Katrin; Brueck, Rigo; Jähne, Andreas; Vach, Kirstin; Ratka-Krüger, Petra (Frontiers in Psychology, 2016)
Background: The success of periodontal therapy depends on the adherence of patients to professional recommendations. The aim of this study was to investigate the influence of a workshop in Motivational Interviewing (MI) on non-surgical periodontal treatment performed by dental students. Material and Methods: In the experimental group patients with periodontitis were treated by students trained in MI, while in the control group patients were treated by students who had not been trained in MI. Clinical oral parameters were assessed by a blinded periodontist in addition to the evaluation of psychological questionnaires given before and after the non-surgical periodontal treatment (six months). Conversations between patients and students were recorded and rated with the Motivational Treatment Integrity Code (MITI-d) by a blinded psychologist. Results: There were 73 patients in the MI group and 99 patients in the control group. The MI group showed significantly higher scores in the MITI-d analysis. Regression analysis showed that there were no significant differences between groups with regard to plaque level, gingival bleeding, pocket depth reduction or bleeding upon probing. However, patients in the MI-group showed significantly higher interdental cleaning self-efficacy than patients in the control group (MI= 19.57+/-4.7; control= 17.38+/-6.01; p=0.016). Conclusions: Teaching MI to dental students resulted in a significant improvement in the self-efficacy of interdental cleaning in patients compared to a control group of non-trained students, but no improvement in other aspects of non-surgical periodontal therapy. The study also showed that an eight-hour workshop with supervision significantly improved the MI-compliant conversations of dental students without requiring more conversation time.